2018
DOI: 10.1038/s41598-018-34145-9
|View full text |Cite
|
Sign up to set email alerts
|

Smoking aggravates ventricular arrhythmic events in non-ischemic dilated cardiomyopathy associated with a late gadolinium enhancement in cardiac MRI

Abstract: Smoking is known to increase cardiovascular events, but the association and mechanisms between smoking and ventricular arrhythmic events in dilated cardiomyopathy (DCMP) are unknown. The purpose of this study is to investigate the hypothesis that smoking is associated with sudden cardiac death (SCD) and ventricular arrhythmia in DCMP patients. We enrolled 378 patients who underwent cardiovascular magnetic resonance imaging (cMRI) and were diagnosed with DCMP at two general hospitals in Korea. The clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Risk factors included in the MAGGIC risk model were proven associated with adverse events in HF patients as well as DCM patients. 16,[30][31][32][33] And we could also infer that these risk factors were associated with left ventricular remodeling in DCM patients as well, for some of these risk factors were previously proven associated with left ventricular remodeling. 6,34,35 Thus, the MAGGIC risk model generates a good combination of these risk factors for predicting adverse events and left ventricular remodeling.…”
Section: Maggic Risk Model and Risk Factors Includedmentioning
confidence: 81%
“…Risk factors included in the MAGGIC risk model were proven associated with adverse events in HF patients as well as DCM patients. 16,[30][31][32][33] And we could also infer that these risk factors were associated with left ventricular remodeling in DCM patients as well, for some of these risk factors were previously proven associated with left ventricular remodeling. 6,34,35 Thus, the MAGGIC risk model generates a good combination of these risk factors for predicting adverse events and left ventricular remodeling.…”
Section: Maggic Risk Model and Risk Factors Includedmentioning
confidence: 81%
“…There is a dearth of direct studies that explores the relationship between smoking and ACMs; it is important to note that some literature [37,38] noted that smoking worsens cardiac diseases, particularly electrical conditions of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking increases inflammation and triggers fibrotic processes, including cardiac fibrosis; this has a strong correlation with systolic dysfunction, diastolic dysfunction and abnormal electrical excitation [34]. A study done in South Korea involving NIDCM patients using Cardiac MRI concluded that smokers had higher fatal ventricular arrhythmic events and poorer outcomes compared to non-smokers [34].…”
Section: Cardiovascular Risk Factors In Patients With Nidcmmentioning
confidence: 99%